2020
DOI: 10.3390/cancers12123552
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus at the Forefront of Cancer Immunotherapy

Abstract: Preclinical and clinical studies dating back to the 1950s have demonstrated that Newcastle disease virus (NDV) has oncolytic properties and can potently stimulate antitumor immune responses. NDV selectively infects, replicates within, and lyses cancer cells by exploiting defective antiviral defenses in cancer cells. Inflammation within the tumor microenvironment in response to NDV leads to the recruitment of innate and adaptive immune effector cells, presentation of tumor antigens, and induction of immune chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 107 publications
(180 reference statements)
1
69
0
1
Order By: Relevance
“…In tumoral cells, NDV replicates in the intra cellular environment with a cytotoxic, necrotic effect or an auto phagocytosis mechanism. Thus, the NVD achieves control in cancer cells, stimulating immunity against tumors 45,93 . It has been shown that NDV is non-pathogenic to humans as it has been used as a treatment against multiple types of cancer without causing serious adverse effects 45,93 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In tumoral cells, NDV replicates in the intra cellular environment with a cytotoxic, necrotic effect or an auto phagocytosis mechanism. Thus, the NVD achieves control in cancer cells, stimulating immunity against tumors 45,93 . It has been shown that NDV is non-pathogenic to humans as it has been used as a treatment against multiple types of cancer without causing serious adverse effects 45,93 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that NDV is non-pathogenic to humans as it has been used as a treatment against multiple types of cancer without causing serious adverse effects 45,93 . In vitro studies in breast, kidney, bone, skin, brain and cervical cancer cells show that NDV causes cancer cell reduction by activating extrinsic and intrinsic pathways of apoptosis 45,[94][95][96][97] . Clinical trials with rNDV have been developed over the years, and more than a dozen of studies have been reported in which lytic NDV strains have been inoculated .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NDV selectively infects, and lyses tumor cells by exploiting defective antiviral defenses in cancer cells. Inflammation within the tumor microenvironment in response to NDV leads to the recruitment of innate and adaptive immune effector cells, presentation of tumor antigens, and induction of immune checkpoints [ 39 ].…”
Section: Introductionmentioning
confidence: 99%